Analisis Tindak Tutur Lokusi dalam Daftar Putar “Zental Health” pada Saluran Youtube Zenius - Novi Amelia Oktaviani; Avita Setiawati; Hidayatul Afifah; Trista Etika Putri; Dita Luluk Safitri; Asep Purwo Yudi Utomo; Limpad Nurrachmad (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Locutionary speech acts are a type of speech act that focuses on the meaning of a sentence. This research is based on speakers whose pronunciation does not emphasize actual speech. The aim of this research is to describe the form and intent of locutionary speech acts in the